Adrenal Dysfunction Caused by Critical Illness and Its Correction by Controlling Body Temperature: Prospective Cohort Study - N. E. Altshuler; N. M. Kruglyakov; M. B. Kutsyi; K. A. Popugaev (Неотложная медицинская помощь, 2024)
BACKGROUND. Critical condition (CC) is defined as any life-threatening condition that requires support of the functions of vital organs and systems to prevent imminent death. From the point of view of the course of CC and the survival of the patient, adequate functioning of the hypothalamic-pituitary-adrenal axis (HPA) is fundamentally important.   AIM OF STUDY. To improve treatment outcomes for critically ill patients requiring temperature management through early diagnosis and timely correction of adrenal dysfunction.   MATERIAL AND METHODS. Of the 59 patients, 45 (76.3 %) patients were diagnosed with adrenal dysfunction upon body temperature management (BTM) caused by critical illness: group I with vascular failure (VF+); in 14 (23.7 %) patients of group II adrenal disfunction wasn’t revealed (VF-).   RESULTS. In group I (VF+) there was a high SOFA score, the highest number of days from the moment of illness to admission to the intensive care unit andinitiation of BTM, the presence of liver dysfunction, and a high level of C-reactive protein. Vascular failure in patients in group I developed earlier than other organ dysfunctions and sepsis. The high level of cortisol in the blood plasma in group II (VF-) was associated with the development of corticoresistance.   CONCLUSIONS. 1. At body temperature management initiation, patients with adrenal dysfunction had a statistically significant high sofa score compared to patients without adrenal dysfunction (8 (5–9); 7 (6–8), respectively, p < 0,05). 2. The number of days from the disease onset to admission to the icu and initiation of body temperature management was statistically significantly high in the group with adrenal dysfunction compared to the group without adrenal dysfunction (20 of 45 patients (44.4 %); 4 of 14 (28.6 %) respectively, p < 0.05). 3. In the development of septic shock in patients with adrenal dysfunction, the criterion for the efficacy of the therapy was stabilization of the patient’s condition: positive hemodynamic response to the introduction of hydrocortisone with reduced doses of noradrenaline and its subsequent cancellation. 4. Despite the fact that the rate of organ dysfunction, sepsis and septic shock were statistically significantly higher (p < 0.05) in the group with adrenal dysfunction and the presence of vascular insufficiency, the performed treatment (hydrocortisone administration) allowed outcomes comparable to these in patients without adrenal dysfunction to be achieved (p > 0.05).